COLD CLIMATE IN THE EASTERN AUSTRALIAN MID TO LATE PERMIAN MAY REFLECT COLD UPWELLING WATERS - Jones A.T.; Frank T.D.; Fielding C.R. (My University, 2006)
A suite of ice-rafted dropstones and glendonites throughout the Permian succession of eastern Australia indicates the cold climate associated with the late Palaeozoic ice age persisted longest in this part of Gondwana. Paradoxically, these cold climate indicators are preserved in transgressive and highstand facies and formed at mid to high latitudes at a time when palaeofloral and sedimentological data suggest equable onshore environments during the intervening lowstands and temperate conditions at the pole. These apparent inconsistencies suggest that eastern Australia was anomalously cold in the context of post-Sakmarian Gondwanan climates, and the distribution of sedimentary indicators could indicate localized cooling by oceanographic processes. Modern upwelling of cold abyssal waters produces the specific physiochemical conditions necessary for ikaite formation, and is likely to have contributed to the development of glendonites in the eastern Australian Permian system. Such upwelling would have locally lowered surface water temperatures such that seasonal sea or river ice could form, which rafted debris across the marine shelf, and a cold-water fauna could develop. This hypothesis is supported by coupled atmosphere-ocean models for the Permian, which suggest that wind systems may have driven upwelling along this section of the Gondwanan coast. Colder conditions dissipated with the onset of the Hunter-Bowen Contractional Event and the transformation of the basin system from an open marine shelf to a foreland basin. This new hypothesis reconciles the prolonged deposition of cold-climate indicators in the eastern Australian Permian with an apparent post-Sakmarian warming elsewhere in Gondwana. © 2005 Elsevier B.V. All rights reserved.
Keywords: COLD CLIMATE INDICATORS; EASTERN AUSTRALIA; GONDWANA; LATE PALAEOZOIC ICE AGE; PALAEOCLIMATE MODELS; PERMIAN; UPWELLING; Paleozoic::Permian; Палеозой::Пермская